Alkaline hydrogen peroxide pretreatment of bamboo residues and its influence on physiochemical properties and enzymatic digestibility for bioethanol production - Ummalyma, Sabeela Beevi; Herojit, Ningthoujam; Sukumaran, Rajeev K. (Frontiers in Energy Research, 2024)
Bamboo is a perennial rapid-growing plant that is given preference for renewable biosources for biofuels and bio-based chemical conversion. Bamboos are rich in cellulose and have highly recalcitrant biomass due to high lignin. Bamboo is abundantly available in Northeastern India and can be utilized as a feedstock biofuels. Here, we evaluated the pretreatment of bamboo residues Dendrocalamus strictus with different concentrations of alkali, hydrogen peroxide, and alkaline hydrogen peroxide and its influence on biomass digestibility for enhancement of sugar recovery with Celic C cellulase enzyme blend. Enzymatic hydrolysis data indicated untreated raw biomass showed a digestibility of 40% after 48 h of incubation. The biomass pretreated with alkali showed a maximum digestibility of 61% obtained from 10% loaded with 0.5% w/v NaOH. Pretreatment of the bamboo with H2O2 shows a maximum digestibility of 75% from biomass loaded with 1% w/v of H2O2. Combinational pretreatment of alkaline hydrogen peroxide showed a maximum efficiency of biomass digestibility of 83% attained from biomass loaded with 1% w/v NaOH-H2O2. Crystallinity index (CrI) analysis showed that CrI increased from 64% to 70.75% in pretreated biomass. FTIR and SEM analysis show changes in functional groups, morphology, and surface of biomass in pretreated biomass. Compositional analysis shows that 68% of lignin removal is obtained from alkaline hydrogen peroxide pretreatment. Cellulose content increased from 52% to 65%, and hemicellulose decreased from 18.6% to 8.6%. Results indicated that the potential possibility of bamboo waste biomass as feedstock for biorefinery products and alkaline hydrogen peroxide pretreatment methods is an efficient strategy for sugar recovery for bioethanol production.